EFFECT OF ELECTRICAL MUSCLE STIMULATION WITH SENSIROMOTOR TRAINING IN FOCAL HAND DYSTONIA - A CASE REPORT (International Journal of Physiotherapy, 2015)
Background: Focal hand Dystonia is shown by involuntary muscle contractions in the arm or hand while writing with a disordered neuroplastic changes in the brain. Symptoms can include lack of co-ordination, cramping and tremor and tend to be specific for each individual. So, the present study evaluates the effect of an integrated approach that is employed to improve functional independence in a patient suffering from focal hand dystonia.Case Description: The benefits of sensorimotor task specific training along with electrical muscle stimulation in the rehabilitation of focal hand dystonia is reported in this study. The treatment protocol is planned according to the problem list of the patient and an intervention of 20 days (1 hour per day, 5 days per week for 4 weeks) is given to the patient.Outcome Variables: Prognosis is observed in Burke-Fahn-Marsden scale, global dystonia scale, Jedynak’s protocol and unified dystonia rating scale before & after the intervention. A Depression anxiety stress scale is also used to assess the psychological status of the patient.Conclusion: Considerable improvement is seen in writing and fine motor skills after the rehabilitation. It is observed that the electrical muscle stimulation in conjunction with sensiromostor task specific training induces excitability in the muscles and improve the clinical function in patient with focal hand dystonia.